New Zealand on the Pacific Frontier: Environment, Economy and Culture - McAloon, Jim (History compass, 2006)
This article reviews the first decades of European activity in New Zealand, a period dominated by resource extraction. It suggests that while much excellent scholarly work has been published on this period, a fuller understanding is by integrating the sometimes historiographically separate themes of environmental history, imperial economic history, and culture contact.